Increased levels of interleukin-8 in BAL fluid from smokers susceptible to pulmonary emphysema. Issue 5 (1st May 2002) - Tanino, M; Betsuyaku, T; Takeyabu, K; Tanino, Y; Yamaguchi, E; Miyamoto, K; Nishimura, M
Abstract : Background: It has previously been shown that smokers with computed tomographic (CT) evidence of subclinical emphysema have signs of neutrophil activation, despite having no appreciable increase in the number of neutrophils in their bronchoalveolar lavage (BAL) fluid. Methods: The levels of the following chemoattractants in BAL fluid from 61 community based older volunteers classified into four groups according to current smoking status and the presence or absence of emphysema were determined: interleukin 8 (IL-8), epithelial neutrophil activating protein 78 (ENA-78) and leukotriene B4 (LTB4 ) which are primarily chemotactic for neutrophils; monocyte chemoattractant protein 1 (MCP-1) and macrophage inflammatory protein-1α (MIP-1α) which are predominantly chemotactic for mononuclear leucocytes. Results: Of the five chemoattractants studied, only the level of IL-8 in BAL fluid clearly distinguished between subjects with and without emphysema among current smokers (median values 34.7 and 12.2 pg/ml, respectively, p<0.01). In addition, the levels of IL-8 and neutrophil elastase-α1 protease inhibitor complex in BAL fluid were significantly correlated ( r =0.65, p<0.01). There was no difference in either the release of IL-8 from cultured alveolar macrophages at 24 hours or the expression of IL-8 messenger RNA of alveolar macrophages in the two groups of current smokers with and without emphysema. Conclusion: An accelerated response of IL-8 to chronic smoking is a factor that characterises those smokers who are susceptible to pulmonary emphysema, although the cellular source of IL-8 remains to be determined.